Biotransformation of the total flavonoid extract of epimedium into icaritin by two thermostable glycosidases from Dictyoglomus thermophilum DSM3960. (June 2021) - Zhang, Shanshan; Luo, Jianianhua; Dong, Yurong; Wang, Zhenzhong; Xiao, Wei; Zhao, Linguo
Graphical abstract: Highlights: DthRha could efficiently hydrolyze the α-1-rhamnosidic bond of epimedium flavonoids. Icaritin preparation by two thermostable enzymes with high productivity. Major parts of total flavonoids extract of epimedium were transformed into icaritin. Abstract: The thermostable GH78 family α-L-rhamnosidase DthRha from Dictyoglomus thermophilum DSM3960 was found to have the ability to remove the α-L-rhamnose moiety that was directly linked to the aglycone by an α-1-rhamnosidic bond at the C-3 position of epimedium flavonoids. It exhibited high specific activity on p- nitrophenyl-α-L-rhamnopyranoside (pNPR) (281.06 U/mg), followed by epimedin C (30.42 U/mg), icariin (9.74 U/mg), baohuoside I (1.02 U/mg) and 2'-O-rhamonosylicariside II (3.74 U/mg). In addition, the thermostable glucosidase Dth3 from Dictyoglomus thermophilum DSM3960, which exhibits β-xylosidase activity and β-glucosidase activity, was purified. The main enzymatic properties of the two thermostable glycosidases were compared, and these glycosidases were successfully utilized in the preparation of pharmacologically active icaritin from the total flavonoid extract of epimedium. Finally, 5 g/L of the total flavonoid extract of epimedium was completely transformed into 207.95 mg/L icaritin at pH 5.5 and 80 °C for a total of 4 h. This is the first report on the efficient biotransformation of the total flavonoid extract of epimedium into icaritin by two thermostable enzymes with high productivity. The cost of icaritin preparation will be substantially reduced by converting all the major ingredients in the total flavonoid extract of epimedium.